Do foodborne polyethylene microparticles affect the health of rainbow trout (Oncorhynchus mykiss)? - Hodkovicova, N; Hollerova, A; Caloudova, H; Blahova, J; Franc, A; Garajova, M; Lenz, J; Tichy, F; Faldyna, M; Kulich, P; Mares, J; Machat, R; et al. (The Science of the total environment, 2021)
Due to the fact that plastic pollution is a global environmental problem of modern age, studies on the impact of these synthetic materials on aquatic, and especially fish organisms, are an important part of the ecosystem and human nutrition. In our study, the toxicity of pristine polyethylene (PE) microparticles (approx. 50 μm) on rainbow trout (Oncorhynchus mykiss) was tested in three different dietary concentrations - 0.5%, 2% and 5%. After six weeks of exposure, various health indices were evaluated. Electron microscopy of the intestine revealed the disintegration of PE particles to <5 μm in size, and thus we concluded that microplastics are able to reach tissues. The haematological profile revealed changes in total red blood cells count and haematocrit (5% PE) which could be associated with spleen congestion observed histologically. The marker of lipid peroxidation was increased in gills suggesting the disruption of balance in antioxidant enzymes capacity and histopathological imaging revealed inflammation in higher PE concentrations. In addition, ammonia was decreased and calcium elevated in biochemical profile, confirming the gill damage. Electron microscopy of the gills showed lesions of lamellae and visible rings around the mucinous cell opening indicating their higher activity. Another injured was the liver tissue, as confirmed by hepatodystrophies and increased expression of pro-inflammatory genes in 2% PE. Impaired innate immunity was confirmed by an increased presence of mucinous cells and a decrease in leukocytes. Kidney damage manifested itself by higher expression of pro-inflammatory cytokines and histopathology. The damage in gills, liver and kidney together correlated with the increased antioxidant capacity of plasma. In conclusion, PE microparticles are able to affect health indices of O. mykiss. The potential problem for aquatic ecosystems and even human consumption should be considered.
Keywords: Electron microscopy; Plastics; Oncorhynchus mykiss; polyethylen; Ecosystem; Plastic; Polyethylene; Antioxidant capacity; Toxicology; Animals; lidé; Humans; zvířata; ekosystém; Immunity; Gills; plastické hmoty; Salmonidae; žábry